Market Transparency, Adverse Selection, and Moral Hazard - Tobias J. Klein; Christian Lambertz; Konrad Stahl (University of Mannheim, Department of Economics, 2014)
We study how seller exit and continuing sellers' behavior on eBay are affected by an improvement in market transparency. The improvement was achieved by reducing strategic bias in buyer ratings. It led to a significant increase in buyer satisfaction with seller performance, but not to an increase in seller exit. When sellers had the choice between exiting—a reduction in adverse selection—and improving behavior—a reduction in moral hazard—, they preferred the latter because of lower cost. Increasing market transparency improved market outcomes.
urn:nbn:de:bsz:180-madoc-372754
Keywords: D47; D83; L15; 330; Anonymous markets; adverse selection; moral hazard; reputation mechanisms; market transparency; market design